AB0513 B and t lymphocytes modifications after belimumab treatment in patients with systemic lupus erythematosus. (12th June 2018) - Regola, F.; Piantoni, S.; Reggia, R.; Kumar, R.; Andreoli, L.; Franceschini, F.; Tincani, A.; Airo', P.
Abstract : Background: B- and T-cell hyper-activation is one of the pathogenic mechanisms of systemic lupus erythematosus (SLE). SLE patients have a severe defect in the B cell tolerance check, resulting in high numbers of autoreactive mature naïve B-cells (CD19 +CD27-IgD+) and of peripheral transitional B-cells (CD19 +38high24high). On the other hand, in patients with active SLE a reduced thymic output with a decreased number of recent thymic emigrants T-cells (RTE; CD4 +CD31+) was demonstrated, whereas repeated antigenic stimulation drives modifications in T-cells subpopulations, with enhanced differentiation into effector memory cells (CCR7-CD45RA-). 1 Belimumab is a monoclonal antibody against soluble BLyS used in the treatment of severe SLE. Although B cells are the main target of this treatment, a BLyS-dependent T-cell activation pathway has also been demonstrated. 2 However, few data are available on the effects of belimumab on circulating B- and T-cell subsets. Objectives: The aim of this study was to characterise B and T-cell phenotype in a cohort of patients with SLE, and to analyse their modifications during belimumab therapy. Methods: Phenotypic analysis of peripheral blood B and T lymphocyte subsets was made by flow-cytometry in 14 SLE patients before the first infusion of belimumab, and after 12 months of treatment. SLEDAI 2K-score was used to determine disease activity: a score ≥6 indicated high disease activity. Sex and age-matched healthy controls were enrolled for the comparisons. Results: At baseline, SLE patients had lower numbers of B- (82 vs 153 cell/µl; p=0.05), T- CD4+ (365 vs 1131 cell/µl; p<0.01), T- CD8+ (340 vs 516 cell/µl; p=0.01), and RTE (95 vs 240 cell/µl; p=0.03) than healthy donors. After treatment there was a decrease of total B lymphocytes (82 vs 19 cell/µl; p<0.01), and particularly of naïve (45 vs 19% of CD19+; p<0.01) and transitional cells (1 vs 0.2 cell/µl; p=0.03). The absolute number of unswitched memory B cells decreased (2.2 vs 1.4 cell/µl; p=0.05), whereas the percentage of switched memory B cells increased (16 vs 44% of CD19+; p<0.01). The absolute number of CD8 +effector memory cells was also reduced (61 vs 53 cell/µl; p=0.05), as well as percentages of RTE (20 vs 10% of CD4+; p=0.01). After 1 year therapy in the only 2 patients with persistent high disease activity the percentages of transitional B cells and unswitched memory cells were higher than in 7 patients in which an initially high disease activity decreased below SLEDAI=6 (9% vs 1%; p=0.03; and 29% vs 6%; p=0.04, respectively). Conclusions: The effects of belimumab on B cell subpopulations are likely to be directly explained by the blockage of soluble BLyS. On the other hand, the effects on the phenotype of T cells are modest and it cannot be excluded that they are indirectly explained by the reduction of disease activity obtained through the therapy. The number of certain circulating B cell subsets might be a marker of response to treatment. References: [1] Piantoni S, et al. Lupus2017. [2] Jacobi AM, et al. Arthritis Rheum2008. Disclosure of Interest: None declared